The Life Journey and Creative Writing of the Yakut Classic Writer A. I. Sofronov: An Experience in Systemizing the History of Studying and Evaluating the Subject Matter - Semyonova, Valentina Grigoryevna; Vasilyeva, Tatiana Nilovna (Journal of History Culture and Art Research, 2018)
The following research paper presents an analysis of the history of studying and evaluating the creative heritage of one of the founders of the Yakut literature A.I. Sofronov. Based on the archive database search and biographical methods, we gained and are sharing an experience in systemizing the periods of life and creative journey of the writer; we also provide a description of these specific time segments without any ideological imperatives. The given research implements and introduces into the scientific use the archive and periodical materials published at the beginning of the 20th century as well as the literary critics materials written by the social activists of the republic and forbidden for a considerable amount of time. The study presents a genuine description of the impact caused by the decrees of the political party, which reflect the political situation in the country, and the impact it had on the evaluation of the writer's works. This paper also contains an analysis of the previous researches on the interpretation and opinions on the creative method of A.I. Sofronov. The research is theoretically and methodologically based on a cultural-historical approach, which suggests that specific cultural-historical circumstances and social life have a formative impact on literature, and a biographical method, according to which a writer’s personal life experience and biography play a key role in study of his creative work. As no literary process is possible without the writers as individuals, it is important to study their creative writing through biographical method in order to develop a specific concept of the national literature history and to single out the periods of its development. The present study justifies that the renown social and creative activist of Yakutia A.I. Sofronov is one of the key figures, whose creative writing played a significant role in forming and establishing Yakut national culture and literature; it also defined the entire trend of its development in the 20th and 21st centuries. The suggested timeline of the life and creative path of the writer is subdivided into six time-periods, which coincide with the social and political changes in the life of the society: I. 1914-1925; II. 1925-1942; III. 1942-1952; IV. 1952-1962; V. 1962-1986; VI. 1986 – present days. As a result, the given research helped to single out the features in studying and evaluating the creative writing journey of the writer covering various periods of the literary and critical works development in Yakutia: the principles and approaches, which remained unknown to reader earlier as well as the real existing literary and social-political events.